Peningkatan Pengetahuan UMKM Pangan tentang Produk Pangan Bergizi, Aman, dan Halal - Rachmawati Widyaningrum; Cita Eri Ayuningtyas; Dyah Suryani; Hesti Khofifah; Siti Mutmainah; Shaumi Natalia Putri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
As part of Micro, Small, and Medium Enterprises (MSMEs), the Culinary Sector is the sector that has the largest contribution to the National Gross Domestic Product at 32.50%. During the Covid-19 pandemic, the MSME business in the culinary industry showed positive growth with an increase in the number of enterprises and their transactions, especially with the internet-based marketing system (online). However, it still has several problems, such as low nutritional value, safety issues, and the product halalness. Tirtonirmolo, a subdistrict that houses 178 food MSMEs, is also experiencing the same problem with the low number of products certified for their safety and halal status. Educational programs were conducted to increase the knowledge of the household food industry in Tirtonirmolo by the principles of nutrition, food safety, and halalness. Through educational programs, knowledge improvement is carried out through an online meeting platform with three topics: improving nutritional food value, safety, and halal food products. Measurement of the increase in knowledge is done by comparing the results of the pre-test and post-test. The measurement results showed that there was an increase in knowledge scores in three aspects, namely nutrition (9.1 points), food safety (11.4 points), and food halalness (13.1 points), with an average of 11.4 points. From the evaluation results, it was found that most of the participants felt that this activity was valuable and applicable and had expectations for follow-up. This educational program can be designed to be carried out ongoing to obtain a more optimal result of increasing knowledge.